PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN BANK SAMPAH INDUK ‘RUMAH HARUM’ DI KELURAHAN ABADIJAYA, KECAMATAN SUKMAJAYA, KOTA DEPOK - Khairunnisa, Hana; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
Waste is a problem that has not been resolved properly in Depok City. To reduce the resulting impact, Rumah Harum Main Waste Bank implements community empowerment in waste management. The aim of the research is to analyze community empowerment in managing the Rumah Harum Main Waste Bank, as well as analyzing supporting and inhibiting factors of community empowerment. The theory used is the stages of community empowerment according to Wrihatnolo and Dwidjowijoto (2007) and community empowerment factors according to Anggraini, Noor, and Said (in Tullatifah, 2020) . This research uses a descriptive qualitative method with data accumulation techniques including observation, interviews, and documentation. The research results show that community empowerment is carried out through three stages: awareness, capacity, and empowerment. Community empowerment in managing the Rumah Harum Main Waste Bank has not been running well. There is one stage of the third stage of empowerment that has not yet been underway, namely at the empowerment stage. Regarding supporting factors of empowerment consists of the involvement of surrounding communities and cooperation with other parties. Inhibiting factors of empowerment consist of indiscipline from waste bank customers and society's inappropriate mindset. Suggestions that can be given are training in making waste recycling products, training for administrators, improving waste bank customer discipline, and outreach involving several community leaders.